On the ``Active spacer and stabilizer'' role of Zn in Cu1-xZnxFe2O4 in the selective mono-N-methylation of aniline: XPS and catalysis study - Vijayaraj, Munusamy; Gopinath, Chinnakonda S. (Journal of Catalysis, 2006)
A systematic catalytic methylation study on ferrospinel materials led to the selective production of N-methylaniline (NMA) with Cu1-xZnxFe2O4. Aniline methylation was carried out on Cu1-xZnxFe2O4 with a feed composition of CH3OH:PhNH2:H2O = 3:1:1 at 513-633 K. NMA was formed selectively on all of the catalyst compositions, with trace amounts of secondary products under most of the conditions. Cu0.5Zn0.5Fe2O4 composition showed high catalytic activity and stability up to 100 h. Although the Cu2+ was responsible for methylation activity, Zn2+ enhanced the overall stability of the catalyst system. XPS investigations revealed that the degree of Cu2+ reduction decreased dramatically from x = 0.05/0.25 to 0.5/0.75 on spent catalysts. TPR studies indicated that the reducibility of Cu2+ decreased from fully reducible at 523 K with Cu-rich compositions to partially reducible at 573 K on x = 0.5. Stable activity observed on Cu0.5Zn0.5Fe2O4 can be attributed to the highly heterogeneous distribution of metal ions. This heterogeneous distribution indicates an important role of zinc, likely as an ``active spacer cum stabilizee' that hinders the reduction of active Cu2+ and contributes to prolonged activity. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: Aniline; Ferrite; N-methylaniline; N-methylation; spacer; stabilizer; surface distribution; TPR; XPS

Autoreduction of cyanoferrate(III) ions in a polymer electrolyte membrane: all solid state electrochemical and spectroscopic investigations - Parthasarathy, Meera; Gopinath, Chinnakonda S.; Pillai, Vijayamohanan K. (Chemistry of Materials, 2006)
The effect of dielectric confinement on proton-coupled electron-transfer behavior and spectroscopic properties of cyanoferrate ions in a polymer electrolyte membrane (Nafion) has been investigated in an ``all-solid-state'' electrochemical cell, using techniques such as cyclic voltammetry, zero current chronopotentiometry, electrochemical impedance, diffuse reflectance infrared Fourier transform spectroscopy (DRIFT), UV-visible spectroscopy, X-ray photoelectron spectroscopy (XPS), and electron spin resonance spectroscopy (ESR). From the above investigations, we found that cyanoferrate(III) ions undergo autoreduction in the ionomer matrix, for which a sulfonate-coupled mechanism has been proposed. This report demonstrates the effectiveness of the micellar interface in tuning the redox potential of the confined ions. A systematic analysis of the cyclic voltammetry and impedance data for the [Fe(CN)(6)](4)(-)- containing Nafion membrane enables the estimation of a standard rate constant for [Fe(CN) 6](4-) oxidation, k(o), as 5.44 x 10(-6) cm/s and a diffusion coefficient, D-o, as 1.3 x 10(-12) cm(2)/s. A similar calculation yields a value of 4.8 x 10(-12) cm(2)/s for the diffusion coefficient of protons and 9.1 x 10(-6) cm/s for the standard rate constant for hydrogen oxidation. The similarity in mass-transfer coefficients calculated for protons and [Fe(CN)(6)](4-) ions suggests a proton-coupled electron-transfer mechanism for the [Fe(CN)(6)](4-)/[Fe(CN)(6)](3-) couple. The results of the above investigations could have direct technological relevance for deciding catalyst materials having redox compatibility with the polymer electrolyte, especially in the preparation of catalyst-coated membranes (wherein the fuel-cell catalyst is directly coated onto the polymer membrane instead of on the carbon support).

Applications of a high performance platinum nanocatalyst for the oxidation of alcohols in water - Maity, Prasenjit; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Green Chemistry, 2009)
Nanoparticles of platinum (NP-Pt), have been synthesized by supporting high nuclearity anionic carbonyl cluster (Chini cluster) on a water soluble anion exchanger, and the performance of this material, 1, as an oxidation catalyst for alcohols in water has been studied. The E-factor for the synthesis of NP-Pt by this method has been calculated and compared with that of other NP-Pt recently reported in the literature. With 1 as a catalyst, oxidations of a variety of primary and secondary alcohols by dioxygen are achieved and high turnover numbers and selectivities are obtained. The performances of 1 in the oxidation of benzyl alcohol and 1-phenylethanol are compared with those of three other platinum catalysts. These are platinum nanoparticles 2 prepared by the hydrogen reduction of [PtCl6](2-) supported on the same water soluble polymer, 5% Pt on carbon, and 5% Pt on alumina, designated as 3 and 4, respectively. 1 has been found to be considerably more active than 2- 4 and also other reported water soluble platinum nanocatalysts. After many turnovers (similar to 1000 and similar to 165 for benzyl alcohol and 1-phenyl ethanol, respectively) partial deactivation (similar to 40%) is observed, but the deactivated catalyst can be fully regenerated by treatment with dihydrogen. The TEM data of fresh, deactivated and regenerated 1 show a correlation between the particle size and activity. A mechanism consistent with this and other experimental observations including XPS data is proposed.

Aminosilicate sol-gel stabilized N-doped TiO2-Au nanocomposite materials and their potential environmental remediation applications - Pandikumar, Alagarsamy; Sivaranjani, Kumarsrinivasan; Gopinath, Chinnakonda S.; Ramaraj, Ramasamy (RSC Advances, 2013)
A facile chemical reduction method to synthesize amine functionalized silicate sol-gel-supported gold-deposited nitrogen-doped Degussa-TiO2 nanocomposite materials (APS/(N-P25-Au)(NCM)) is reported and the materials are characterized by DRS, PL, XRD, TEM, Raman, XPS and BET surface area analysis. The application of the synthesized APS/(N-P25-Au)(N)CM towards environmental remediation processes are investigated by studying the catalytic oxidation of carbon monoxide (CO) and photocatalytic reduction of toxic mercuric (Hg(II)) ions. The catalytic and photocatalytic activity of the prepared catalysts are found to be in the order of APS/(N-P25-Au)(NCM) >> APS/(P25-Au)(NCM) > N-P25 > P25. The enhanced catalytic and photocatalytic activities of the APS/(N-P25-Au)(NCM) can be attributed to the synergistic effect of Au-nps and N-doped P25. The catalytic activities of the APS/(N-P25-Au)(NCM) are very promising in the field of green technology for the environmental cleaning applications.

Ambient oxidation of benzene to phenol by photocatalysis on Au/Ti0.98V0.02O2: role of holes - Devaraji, Perumal; Sathu, Naveen K.; Gopinath, Chinnakonda S. (ACS Catalysis, 2014)
A potential photocatalyst with 2 atom % vanadium incorporated into the 1 lattice of disordered mesoporous titania, Ti0.98V0.02O2, (TV2) was synthesized. Au was deposited on TV2 (Au/TV2) through a photodeposition method. Structural, microscopy, and spectroscopy techniques support the incorporation of vanadium into the TiO2 lattice, and Au was deposited on the surfaces of TV2. Photocatalytic oxidation of benzene was conducted at ambient temperature under UV and/or visible light to demonstrate the catalytic activity of the Au/TV2 catalyst. The TV2 lattice exhibits a quantum jump in benzene to phenol oxidation compared to that of TiO2, highlighting the importance of V for oxidation. Introduction of Au onto TV2 further increases the benzene to phenol oxidation and phenol yield by a factor of 2 under UV light compared to those of bare TV2. No significant phenol production was observed in visible light with or without gold, indicating the role of gold is indirect toward charge separation and electron storage. Nano gold clusters on TV2 selectively store photoexcited electrons and in turn maximize holes utilization on TiO2. The high photocatalytic activity of Au/TV2 is mainly attributed to the presence of Schottky junctions, disordered mesoporosity, and short diffusion lengths for charge carriers.
Keywords: nano gold; phenol; Photocatalysis; Schottky junction; titania; Vanadium

Attempt to correlate surface physics and chemical properties : molecular beam and Kelvin probe investigations of Ce 1-x Zr x O 2 thin films - Kolekar, Sadhu K.; Dubey, Anjani; Date, Kalyani S.; Datar, Suwarna; Gopinath, Chinnakonda S. (Physical Chemistry Chemical Physics, 2016)
What is the correlation between physical properties of the surfaces (such as surface potential, electronic nature of the surface), and chemical and catalysis properties (such as chemisorption, sticking probability of surface)? An attempt has been made to explore any correlation that might exist between the physical and chemical properties of thin film surfaces. Kelvin probe microscopy (KPM) and the molecular beam (MB) methods were employed to carry out the surface potential, and oxygen adsorption and oxygen storage capacity (OSC) measurements on Ce1−xZrxO2 thin films. A sol–gel synthesis procedure and spin-coating deposition method have been applied to make continuous nanocrystalline Ce1−xZrxO2 (x = 0–1) (CZ) thin films with uniform thickness (35–50 nm); however, surface roughness and porosity inherently changes with CZ composition. MB studies of O2 adsorption on CZ reveal high OSC for Ce0.9Zr0.1O2, which also exhibits highly porous and significantly rough surface characteristics. The surface potential observed from KPM studies varied between 30 and 80 mV, with Ce-rich compositions exhibiting the highest surface potential. Surface potential shows large changes after reduction or oxidation of the CZ film demonstrating the influence of Ce3+/Ce4+ on surface potential, which is also a key to catalytic activity for ceria-based catalysts. The surface potential measured from KPM and the OSC measured from MB vary linearly and they depend on the Ce3+/Ce4+ ratio. More and detailed studies are suggested to arrive at a correlation between the physical and chemical properties of the surfaces.

Ambient CO oxidation on in-situ generated Co3O4 spinel surfaces with random morphology - Dubey, Anjani; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S. (ChemistrySelect, 2017)
The influence of the Co3O4 morphology on its redox behavior and catalytic performance in the CO oxidation reaction is studied. Three different Co3O4 morphologies were synthesized by precipitation and hydrothermal methods. TEM and SEM observations clearly show the different obtained morphologies: rods, wires and a mixture of plates and cubes. The textural properties depend on the morphology and the redox ones on the particle size. XRD analysis reveals a spinel structure in all solids but a preferential exposition of the [110] plane is presented in the Co3O4 rods. This preferential exposition, along with its higher specific surface area provides the rods with more efficient oxygen storage capacity resulting in an excellent catalytic performance compared to the other two morphologies.

Aqueous methanol to formaldehyde and hydrogen on Pd/TiO2 by photocatalysis in direct sunlight: structure dependent activity of nano-Pd and atomic Pt-coated counterparts - Nalajala, Naresh; Salgaonkar, Kranti N.; Chauhan, Inderjeet; Mekala, Siva Prasad; Gopinath, Chinnakonda S. (ACS Applied Energy Materials, 2021)
In the present investigation, facet-controlled Pd nanoparticles with nanocube (Pd-NC) and truncated octahedron (Pd-TO) morphologies, and their counterparts with half-a-monolayer of atomic Pt coated (0.5 theta(Pt)-Pd-NC and 0.5 theta(Pt)-Pd-TO) surfaces were prepared. All of them were characterized and evaluated as cocatalyst after supporting them on commercial titania (P25) (Pd-NC/P25, Pd-TO/P25, 0.5 theta(Pt)-Pd-NC/P25, and 0.5 theta(Pt)-Pd-TO/P25) under direct sunlight and/or one sun conditions for the oxidation of methanol to formaldehyde along with solar hydrogen production. Pd-NC/P25 shows higher activity for hydrogen generation compared to Pd-TO/P25; however, activity reversal occurs with the above cocatalysts, but, after Pt-coating with further enhanced activity. The highest conversion of methanol (0.2 mu mol/h.mg) to 100% selective formaldehyde was observed with 0.5 theta(Pt)-Pd-TO/P25, while other catalysts show significantly lower methanol conversion in the following order: 0.5 theta(Pt)-Pd-TO/P25 > 0.5 theta(Pt)-Pd-NC/P25 > Pd-NC/P25 > Pd-TO/P25. Pt-coated on (111) facets of Pd-TO simulates the activity associated as that of Pt(111) facets and demonstrating the highest and facet dependent activity. The present study is truly in resonance with exploiting the surface properties for heterogeneous catalysis, and highlights that less than a monolayer of Pt is sufficient to simulate the activity as that of bulk Pt. It is worth exploring this concept to other metals and substrates too.
Keywords: heterogeneous catalysis; Nanomaterials; Oxidation; Photocatalysis; surface modification

Aqueous glycerol to glyceric acid and green hydrogen by visible-light-driven photocatalysis with Ni/Co(PO4)2-TiO2: parallel utilization of holes and electrons - Nivedhitha, Thazhath R.; Bajpai, Himanshu; Oommen, Jiffin Varghese; Abraham, Athira; Chauhan, Inderjeet; Gopinath, Chinnakonda S. (ACS Sustainable Chemistry & Engineering, 2024)
Replacing the kinetically sluggish oxygen evolution reaction (OER) with the oxidation of an abundantly available organic molecule to value-added product(s) (VAPs) at low voltage along with the hydrogen evolution reaction (HER) is a big challenge in water splitting, either by electrolysis or sunlight-driven photocatalysis. Glycerol oxidation to a VAP is kinetically fast, compared to an OER, and offers hope to enhance sunlight-driven water splitting to hydrogen by the concurrent utilization of holes and electrons. Mixed bimetal phosphates of Co and Ni (CoxNiy(PO4)(2) (CoNiP)) with different Co:Ni ratios (10:0, 7:3, 5:5, 3:7, and 0:10) were integrated with TiO2 to generate final photocatalyst composites (x wt % CoNiP with TiO2) and employed for concurrent photocatalytic HER and glycerol oxidation. Irrespective of the weight ratios of CoNiP and TiO2, any TiO2-CoNiP composite showed better photocatalytic activity for the HER and glycerol oxidation compared to virgin TiO2. The highest HER as well as selectively generated glyceric acid yield was observed to be 54 and 67 mmol/g, respectively, after 25 h of reaction under 1 sun conditions with TiO2-CoNiP-5:5. An increase in catalytic activity can be attributed to the formation of p-n heterojunctions of the constituent component along with uniform distribution of CoNiP to effectively utilize the charge carriers for redox reactions. Highly selective oxidation of glycerol to glyceric acid (85%), along with other minor products, is also demonstrated, which offers further scope to use solar light to generate VAPs in a sustainable manner. A simple comparison of H-2 yield and all oxidized products together indicates the better utilization of holes for the latter, and hence, there is scope to increase HER and possibly the whole photocatalytic activity.
Keywords: biomass component; earth-abundantmaterial; energy conversion; organicvalorisation; water splitting